2018
DOI: 10.4014/jmb.1712.12052
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Effect of Retro-2.1 against Herpes Simplex Virus Type 2 In Vitro

Abstract: could inhibit HSV-2 infection, with 50% inhibitory concentrations of 5.58 µM and 6.35 µM in cytopathic effect inhibition and plaque reduction assays, respectively. The cytotoxicity of Retro-2.1 was relatively low, with a 50% cytotoxicity concentration of 116.5 µM.We also preliminarily identified that Retro-2.1 exerted the antiviral effect against HSV-2 by a dual mechanism of action on virus entry and late stages of infection. Therefore, our study for the first time demonstrated Retro-2.1 as an effective antivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 49 publications
(89 reference statements)
0
15
0
Order By: Relevance
“…In the natural environment, the main host of HSV infection is human, but it has a full susceptibility to infect cells in the laboratory environment. Previous literatures [32,33] have shown that HSV-2 infection models in vitro can be established on various cell lines, such as human embryonic lung fibroblasts (MRC-5), human endometrial adenocarcinoma cells (HEC-1-A), human cervical cancer cells (Hela), human lung cancer cells (A549), African green monkey kidney cells (Vero), and milk hamster kidney cells (BHK). Among them, Vero cells are classic cell lines for virus amplification.…”
Section: Discussionmentioning
confidence: 99%
“…In the natural environment, the main host of HSV infection is human, but it has a full susceptibility to infect cells in the laboratory environment. Previous literatures [32,33] have shown that HSV-2 infection models in vitro can be established on various cell lines, such as human embryonic lung fibroblasts (MRC-5), human endometrial adenocarcinoma cells (HEC-1-A), human cervical cancer cells (Hela), human lung cancer cells (A549), African green monkey kidney cells (Vero), and milk hamster kidney cells (BHK). Among them, Vero cells are classic cell lines for virus amplification.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have previously shown that Retro-2 and its analogs can reduce Leishmania, polyomavirus, and papillomavirus infections, as well as inhibit Shiga toxin trafficking in cells (Noel et al, 2013;Carney et al, 2014;Craig et al, 2017). Recent reports have also investigated the effect of Retro-2 derivatives on HSV2 infections (Dai et al, 2018). A majority of these studies have focused primarily on Retro-2 derivatives, and at present, less is understood about the antipathogenic potential of Retro-1 and its derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…Recent elegant studies have surprisingly revealed that Retro-2 indeed affects ER functions, which in turn affects trafficking events at the EE/TGN interface (Morgens et al, 2019;Forrester et al, 2020). However, observations that Retro-2 blocks the entry of several viruses at the cell membrane (Dai et al, 2018;Shtanko et al, 2018), in which Stx5 is not expressed, suggest that the small compound additionally exerts Stx5-independent inhibitory effects at sites other than the EE/TGN and ER. Our results reveal that the MT network is a new ER/Golgi-independent cellular target of Retro-2.…”
Section: Discussionmentioning
confidence: 99%